The detection of colistin resistance in carbapenem resistant Klebsiella pneumoniae isolates - Koçer, Ipek; Zer, Yasemin; Buyuktas, Ayse (International Journal of Advances in Medicine, 2021)
Background: Infections that develop with resistant Klebsiella pneumoniae have been associated with high morbidity and mortality. Problems in the treatment of these infections have required the use of new treatment options such as colistin in recent years. This study was carried out to contribute to routine applications by investigating the compatibility of methods commonly used in determining colistin susceptibility with the gold standard broth microdilution (BMD) method. Methods: Colistin MIC values were determined by BMD, broth microdilution based commercial kit (Sensititre, ThermoFisher, USA), Vitek2 (bioMerieux, France) and gradient test (Bioanalyse, Turkey) in 128 carbapenem resistant K. pneumonaie strains isolated from various clinical samples sent from July 2018 to July 2019 to the microbiology laboratory. Results: According to the BMD method, 62 (48.4%) of the isolates were susceptible and 66 (51.6%) were colistin resistant. Accepting BMD method as reference, very large error (to find a susceptible result in a reference test as susceptible) and large error (to detect a susceptible result in a reference test as resistant) ratios in broth microdilution based commercial kit, automated system and gradient test were found respectively as 0%, 15.1, 18.1 and 0, 6.4 and 9.6%. According to the ISO performance criteria, the commercial kit shows "acceptable performance" while the other two tests have a very large error rate of >10% and are considered as "unacceptable performance". Conclusions: It was concluded that the ready kit we tested in laboratories with heavy workload could be used to determine the colistin susceptibility and the result determined in automated systems should be confirmed.